Studi Etnomatematika Masjid Agung Syahrun Nur di Tapanuli Selatan untuk Pembelajaran Bangun Datar dan Ruang - Siregar, Rosmita Sari SIregar; Simbolon, Antonius KAP (Universitas Cokroaminoto Palopo, 2025)
This study examines ethnomathematics exploration in the architecture of Nurul Anwar Mosque as a way for students of MTs. Mambaul Ulum Banjarejo to learn geometry. The architectural elements of this mosque reflect various mathematical concepts, such as plane shapes (rectangle, rhombus, circle) and solid shapes (half sphere, cylinder, cuboid), and geometric transformations (rotation, reflection). This study uses a qualitative descriptive approach that uses ethnomathematics exploration. Data were collected through observation, interviews, documentation, and geometric measurements. The results of the study indicate that geometric elements of the mosque can be integrated into mathematics learning to improve students' understanding of geometric concepts contextually and applicatively. This approach not only makes learning more relevant and interesting, but also preserves local cultural values. In culture-based education, using ethnomathematics can strengthen students' identity in Islamic education and instill an appreciation for cultural heritage and can improve understanding of mathematics learning.